2014
DOI: 10.1093/cvr/cvu104
|View full text |Cite
|
Sign up to set email alerts
|

Sphingosine kinase 1 expressed by endothelial colony-forming cells has a critical role in their revascularization activity

Abstract: The up-regulation of SphK1 and S1P-dependent pathways is critical for the angiogenic/vasculogenic activity of ECFCs. The identification of this pathway provides attractive targets to optimize cell-based therapy for revascularization in ischaemic diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 42 publications
4
37
1
Order By: Relevance
“…6D). Furthermore, the expression of Bace2 and ApoE, both of which have been verified by us and by other researchers to be E-box genes that contain non-canonical E-box motifs in their promoter regions61, was also altered in the hippocampus of aged APP/PS1dE9 mice at ZT5, ZT11, and ZT17 (Fig. 6C).…”
Section: Resultssupporting
confidence: 78%
“…6D). Furthermore, the expression of Bace2 and ApoE, both of which have been verified by us and by other researchers to be E-box genes that contain non-canonical E-box motifs in their promoter regions61, was also altered in the hippocampus of aged APP/PS1dE9 mice at ZT5, ZT11, and ZT17 (Fig. 6C).…”
Section: Resultssupporting
confidence: 78%
“…8 S1P promotes initial sprouting of capillary-like structures by endothelial cells in vitro 13 and synergistically acts with basic fibroblast growth factor for induction of in vitro angiogenesis. 63 In addition, S1P plays a crucial role in stabilizing neovessels in arteriogenesis via the recruitment of mural cells and regulation of endothelial cell-cell junctions.…”
Section: Figmentioning
confidence: 99%
“…While these lipids can have similar effects on cellular response, they possess distinct chemical backbones, mechanisms of synthesis and degradation, and signaling pathways mediated by a discrete set of G-proteincoupled receptors (GPCRs). LPA and S1P predominantly act extracellularly on their GPCRs and can directly regulate cell survival, 2,4,5 differentiation, 2,6-8 cytokine secretion, 9,10 proliferation, [11][12][13] and migration 2,12,13 -each of the important functions that must be considered in regenerative medicine.…”
Section: Introductionmentioning
confidence: 99%
“…Here, we demonstrated that both SK1 and SK2 expressed by H-MVEC have a critical role in capillary morphogenesis of MAB cultured together with H-MVEC in Matrigel. Intriguingly, a recent report demonstrated that the up-regulation of SK1 in endothelial colony-forming cells induced by bone marrow mesenchymal stem cells is critical for their angiogenic/vasculogenic activity [35], supporting the view that a mutual communication between endothelial and mesenchymal cells takes place promoting the formation and the stabilization of new vessels. Although SK1 and SK2 have been often reported to have distinct biological functions based on their different localization inside the cell and tissue distribution [4], in this study, both isoforms were found to be involved, although at a different extent, in the observed biological processes.…”
Section: Discussionmentioning
confidence: 74%